Role of confining pressure on the hydraulic properties of compacted soil - Tanuwidjaja, Samuel Winson (Nanyang Technological University, 2021)
The effects of confining pressure on the hydraulic properties of two types of compacted soils, namely Sand-Kaolin and Sand-Kaolin-Mica, are investigated. The compacted soil specimens are saturated, consolidated by net confining pressures of 50 kPa and 200 kPa separately, and subsequently suction-dried to generate the drying SWCCs. The drying SWCC corresponding to zero confining pressure is derived from the results of Zhao (2020). The SWCCs are then be compared in terms of their key parameters namely air-entry value (AEV), geometric standard deviation (s) and inflection point (ψ_m), especially those that correspond to the second sub-curve of the bimodal SWCC. For Sand-Kaolin, the 2nd AEV increases with increasing confining pressure, whereas the 2nd geometric standard deviation and the 2nd inflection point decreases linearly with increasing confining pressure. These relationships between the variation in Sand-Kaolin’s SWCC with varying confining pressures are further supported by the results of the pore-size distribution (PSD) of the Sand-Kaolin specimens. For Sand-Kaolin-Mica, the 2nd AEV and the 2nd geometric standard deviation decreases linearly with increasing confining pressure, while the 2nd inflection point increases linearly with increasing confining pressure. PSD data cannot be used to justify the variations in Sand-Kaolin-Mica’s SWCC as the elastic nature of the mica particles negates the effects of confining pressure on the soil structure once the confining pressure is removed. However, inferences are made with regards to the effects of confining pressure on mica-influenced soil structure, which may help explain the macro-scale behaviour exhibited in the SWCC.